Brain–Computer Interface-Robot Training Enhances Upper Extremity Performance and Changes the Cortical Activation in Stroke Patients: A Functional Near-Infrared Spectroscopy Study - Liu, Lingyu; Jin, Minxia; Zhang, Linguo; Zhang, Qiuzhen; Hu, Dunrong; Jin, Lingjing; Nie, Zhiyu (Frontiers in Neuroscience, 2022)
Introduction: We evaluated efficacy of Brain Computer Interface（BCI） training to explore the hypothesized beneficial effects of physiotherapy alone in chronic stroke patients with moderate or severe paresis. We also focus on the neuroplastic changes in the primary motor cortex(M1)after BCI training. Methods: Eighteen hospitalized chronic stroke patients with moderate or severe motor deficits were participated in this study. Patients were operated 20 sessions and followed up after one month. Functional assessments were performed at five points: pre1-, pre2-, mid-, post-training and one-month follow-up.Wolf Motor Function Test (WMFT) was used as the primary outcome measure, while, Fugl-Meyer Assessment (FMA), its wrist and hand（FMA-WH）sub-score and its shoulder and elbow (FMA-SE) sub-score served as secondary outcome measures. Neuroplastic changes were measured by functional near-infrared spectroscopy (fNIRS) at baseline and after 20 sessions BCI training. Pearson correlation analysis was used to evaluate functional connectivity(FC) across time points. Results: Compare to the baseline, better functional outcome was observed after BCI training and one-month follow-up, including a significantly higher probability of achieving a clinically relevant increase in the WMFT full score(ΔWMFT score= 12.39 points,F=30.28, P<0.001)、WMFT completion time（ΔWMFT time=248.39seconds,F=16.83，P<0.001）and FMA full score (ΔFMA-UE = 12.72 points, F=106.07, P <0.001)、FMA-WH sub-score （ΔFMA-WH=5.6points, F=35.53, P<0.001）and FMA-SE sub-score （ΔFMA-SE=8.06points, F=22.38, P <0.001）. Compare to the baseline, after BCI training the FC between the ipsilateral M1 and the contralateral M1 was increased（P<0.05）,which was the same as the FC between the ipsilateral M1 and the ipsilateral frontal lobe，and the FC between the contralateral M1 and the contralateral frontal lobe was also increased（P <0.05）. Conclusion: The findings demonstrate that BCI-based rehabilitation could be an effective intervention for motor performance of patients after stroke with moderate or severe upper limb paresis and represents a potential strategy in stroke neurorehabilitation. Our results suggested that FC between ipsilesional M1 and frontal cortex might be enhanced after BCI training.